2016
DOI: 10.1111/jam.13158
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-associated bile acid deconjugation accelerates hepatic steatosis in ob/ob mice

Abstract: We provided evidences that changes in the gut microbiota and their metabolites can alter the profile of BAs, thereby providing a mechanism by which an altered microbiota profile contributes to the development of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 50 publications
1
37
0
1
Order By: Relevance
“…Mice lacking expression of FXR in the intestine also have decreased insulin resistance and lower fatty livers than their wild-type counterparts 79, 82 . A recent study found that ob/ob mice had altered gut microbiota compositions, less taurine-conjugated bile acids, increased intestinal FXR expression levels, and elevated FXR signaling compared to their lean ob/+ littermates 84 , in agreement with the studies in tempol-treated and FXR intestine-deficient mice 79 .…”
Section: Fxr Mediates the Influence Of Gut Microbiota On Nafld Develosupporting
confidence: 72%
“…Mice lacking expression of FXR in the intestine also have decreased insulin resistance and lower fatty livers than their wild-type counterparts 79, 82 . A recent study found that ob/ob mice had altered gut microbiota compositions, less taurine-conjugated bile acids, increased intestinal FXR expression levels, and elevated FXR signaling compared to their lean ob/+ littermates 84 , in agreement with the studies in tempol-treated and FXR intestine-deficient mice 79 .…”
Section: Fxr Mediates the Influence Of Gut Microbiota On Nafld Develosupporting
confidence: 72%
“…During normal enterohepatic circulation, primary bile acids, synthesized by the liver, undergo deconjugation to secondary bile acids by the gut microbiota . Because the primary bile acids are preferential ligands for FXR and secondary bile acids are preferential ligands for TGR5, this provides an interesting mechanism by which gut microbes can modulate bile acid signaling properties (Figure 1E).…”
Section: Mucosal Atrophy Central Line Infection–driven Liver Injurymentioning
confidence: 99%
“…However, differentiating between the direct effects of diet and dietary components vs. changes in host metabolic health (e.g., glucose homeostasis, insulin resistance, or overt diabetes) on microbial ecology has not been systematically investigated. Studies in rodent models of diabetes, including ob/ob mice and Zucker diabetic fatty rats, have identified differences in the gut microbiota between mutant and wild-type animals fed similar diets (24,25,50,61). Although these models control for diet type, the insulin resistance and diabetes phenotype in these animals are driven through defects in leptin production or leptin signaling, which are extremely rare in the pathogenesis of obesity and type 2 diabetes mellitus (T2DM) in humans.…”
Section: Introductionmentioning
confidence: 99%